2019
DOI: 10.3390/antiox8040107
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Special Issue: Peroxiredoxin 6 as a Unique Member of the Peroxiredoxin Family

Abstract: The peroxiredoxins, first discovered about 30 years ago, are the most recently described family of ubiquitously expressed antioxidant enzymes [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…PRDX6, as an antioxidant enzyme, could reduce cellular peroxides including short chain hydroperoxides and phospholipid hydroperoxides through its GPx activity, which could protect cells against oxidative stress [ 2 , 3 , 7 ]. There had been reported that inhibition or deficiency of PRDX6 could increase the intracellular oxidative stress and cause the cell injury [ [39] , [40] , [41] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRDX6, as an antioxidant enzyme, could reduce cellular peroxides including short chain hydroperoxides and phospholipid hydroperoxides through its GPx activity, which could protect cells against oxidative stress [ 2 , 3 , 7 ]. There had been reported that inhibition or deficiency of PRDX6 could increase the intracellular oxidative stress and cause the cell injury [ [39] , [40] , [41] ].…”
Section: Discussionmentioning
confidence: 99%
“…The peroxiredoxins (PRDXs) are a ubiquitous family of highly conserved enzymes that use the thiol groups of their redox-active cysteines (Cys) to catalyze the reduction of peroxides, including hydrogen peroxide or other hydroperoxides [ [1] , [2] , [3] ]. The PRDXs are classified into two categories, 1-Cys and 2-Cys, based on whether the protein contains one or two conserved cysteine residues directly involved in catalysis [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%
“…Prdx5 forms an intramolecular disulfide bond between the C P and C R, within one Prdx molecule and is returned to its reduced form though the action of Trx [ 65 ]. Prdx6 lacks the C R and is thus classified as a 1-Cys Prdx [ 66 , 67 ]. In contrast to the dependence of the reduction of Prdx1–5 on Trx, the disulfide bond in the oxidized form of Prdx6 is reduced by glutathione S-transferase π isoform (GSTπ) [ 68 ].…”
Section: Prdxsmentioning
confidence: 99%
“…Glutathione peroxidase (GPx) and peroxiredoxins (PRX) correspond to the most efficient peroxidases from the cellular point of view and in according to the literature mammals exhibit six PRX groups, in addition to expanding the PRX1 group into four closely related subgroups (PRX1-4) plus PRX5 and PRX6 [18][19][20][21][22]. Moreover, these enzymes utilize GSH and GSH S-transferase (GST) for reduction and resolution of their oxidized peroxidative cysteines (Cys) [23,24].…”
Section: Introductionmentioning
confidence: 99%